2020
DOI: 10.3389/fphy.2020.624779
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Emission Infrared Spectra of Protein Solutions in Low Concentrations

Abstract: In this work, based on the method of infrared emission spectroscopy, the study of emission spectra of interferon-gamma (IFNγ) solution in a mixture or surrounded by three low-concentration solutions (IFNγ, antibodies to IFNγ, glycine buffer) or water control was performed. First of all, the solutions of low concentrations themselves were studied. It was shown that low-concentration solutions of IFNγ and antibodies to IFNγ had lower emission intensity in three spectral bands near 800, 1,300 and 2000 cm−1 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
2
15
0
4
Order By: Relevance
“…Another possible mechanism is mediated by the emission of waves. This mechanism is consistent with the results of our previous research, which showed the presence of radiation in extremely diluted solutions of antibodies to IFNγ in the IR region [16], and has also been attested by other research groups [65,66]. Although the mid-IR range carries information about intramolecular structure, it depends, in part, on intermolecular binding.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Another possible mechanism is mediated by the emission of waves. This mechanism is consistent with the results of our previous research, which showed the presence of radiation in extremely diluted solutions of antibodies to IFNγ in the IR region [16], and has also been attested by other research groups [65,66]. Although the mid-IR range carries information about intramolecular structure, it depends, in part, on intermolecular binding.…”
Section: Discussionsupporting
confidence: 92%
“…The contactless effect of radiation of some systems on others has been known for a long time. Research in this field is ongoing, both in the field of biology [60,61] and in physical chemistry [16,62,63]. Presently, it would be logical to consider two possible mechanisms underlying the effect of contactless impact.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations